PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DAN OPTIMALISASI LAHAN KOSONG DENGAN PENANAMAN BIBIT SERTA PENERAPAN ZERO WASTE DI DESA WAJAGESENG - Cahyani, Ismira Dwi; Aliya, Zafirah; Susanti, Yunita Widya; Oktapiandi, Dinda Maelani; Wardana, Budi; Karina, Karina; Ramadhan, Fardiansyah; Puspita, Kharisma Chandra; Pratama, Sam Adya Diva; Hadi, Yusron (Jurnal Wicara, 2024)
Kuliah Kerja Nyata (KKN) is a form of service of higher education institutions to the community carried out by the University of Mataram (Unram). This activity is carried out by providing opportunities for students and lecturers to be directly in the field as a team in a village or a certain location. The general purpose of this KKN activity is to answer the various issues that have been raised above and realize the Peseng Preparatory Village (Wajageseng) into an economically and environmentally sustainable village through the application of green economy principles and community empowerment. Community empowerment through the development and optimization of vacant land is one of the important strategies in increasing the independence and welfare of village communities. Unused vacant land is often ignored and not used effectively, even though the potential is very large to be developed into useful resources. Wajageseng Village, located in Kopang District, Central Lombok Regency, is an example of a village that has great potential in community empowerment through the development of vacant land. In this context, planting seedlings and implementing zero waste are very relevant strategies to improve the welfare of the community and the environment. Planting seedlings can not only increase fruit production, but it can also increase public awareness about the importance of effective and efficient land use. In addition, the implementation of zero waste can help reduce waste and improve environmental quality, so that people can live more balanced and sustainable. The purpose of this activity is to increase public awareness of the importance of environmental management, improve the quality of life of the community through the development and optimization of vacant land, as well as reduce the volume of waste produced by the community. This activity lasted for 52 days, from July 2nd to August 22nd. Involving students and the local community so that this program runs smoothly. Planting 300 seedlings on vacant land and making 5 garbage bins with location placement, namely 3 at the village office, 1 at the head of the hamlet, and 1 at the health center.